Peripheral injury of pelvic visceral sensory nerves alters GFRα (GDNF family receptor alpha) localization in sensory and autonomic pathways of the sacral spinal cord - Forrest, Shelley L.; Payne, Sophie C.; Keast, Janet R.; Osborne, Peregrine B. (Frontiers in Neuroanatomy, 2015)
GDNF (glial cell line-derived neurotrophic factor), neurturin and artemin use their co-receptors (GFRα1, GFRα2 and GFRα3, respectively) and the tyrosine kinase Ret for downstream signalling. In rodent dorsal root ganglia (DRG) most of the unmyelinated and some myelinated sensory afferents express at least one GFRα. The adult function of these receptors is not completely elucidated but their activity after peripheral nerve injury can facilitate peripheral and central axonal regeneration, recovery of sensation, and sensory hypersensitivity that contributes to pain. Our previous immunohistochemical studies of spinal cord and sciatic nerve injuries in adult rodents have identified characteristic changes in GFRα1, GFRα2 or GFRα3 in central spinal cord axons of sensory neurons located in dorsal root ganglia. Here we extend and contrast this analysis by studying injuries of the pelvic and hypogastric nerves that contain the majority of sensory axons projecting to the pelvic viscera (e.g., bladder and lower bowel). At 7 d, we detected some effects of pelvic but not hypogastric nerve transection on the ipsilateral spinal cord. In sacral (L6-S1) cord ipsilateral to nerve injury, GFRα1-immunoreactivity (IR) was increased in medial dorsal horn and CGRP-IR was decreased in lateral dorsal horn. Pelvic nerve injury also upregulated GFRα1- and GFRα3-IR terminals and GFRα1-IR neuronal cell bodies in the sacral parasympathetic nucleus that provides the spinal parasympathetic preganglionic output to the pelvic nerve. This evidence suggests peripheral axotomy has different effects on somatic and visceral sensory input to the spinal cord, and identifies sensory-autonomic interactions as a possible site of post-injury regulation.